Culturally sensitive palliative care in humanitarian action: Lessons from a critical interpretive synthesis of culture in palliative care literature. Issue 4 (August 2022) - Schuster-Wallace, C.J.; Nouvet, E.; Rigby, I.; Krishnaraj, G.; de Laat, S.; Schwartz, L.; Hunt, M.
Abstract: Objective: There is growing recognition of the importance of increasing preparedness for and the provision of palliative care in humanitarian crises. The primary objective of this review is to interpret the existing literature on culture and palliative care to query the recommendation that humanitarian healthcare providers, teams, and organizations integrate palliative care into their practice in ways that are attentive to and respectful of cultural differences. Methods: A critical interpretive synthesis was applied to a systematic literature review guided by the PRISMA framework. Analysis was based on directed data extraction and was team based, to ensure rigor and consistency. Results: In total, 112 articles covering 51 countries and 9 major worldviews met inclusion criteria. This literature describes culture as it influences perspectives on death and dying, expectations of palliative care, and challenges to providing culturally sensitive care. A key pattern highlighted in articles with respect to the culture and palliative care literature is that culture is invoked in this literature as a sort of catch-all for non-white, non-Christian, indigenous practices, and preferences for palliative care. It is important that humanitarian healthcare providers and organizations aiming to enact their commitment of respect for all persons through attention to potential culturally specific approaches to pain management, suffering, and dying in specific crisis settings do so without reproducing Othering and reductionistic understandings of what culturally sensitive care in humanitarian crises settings involves. Significance of results: This paper clarifies and unpacks the diverse influences of culture in palliative care with the goal of supporting the preparedness and capacity of humanitarian healthcare providers to provide palliative care. In doing so, it aids in thinking through what constitutes culturally sensitive practice when it comes to palliative care needs in humanitarian crises. Providing such care is particularly challenging but also tremendously important given that healthcare providers from diverse cultures are brought together under high stress conditions.